Vertical Artifacts as Lung Ultrasound Signs: Trick or Trap? Part 2‐ An Accademia di Ecografia Toracica Position Paper on B‐Lines and Sonographic Interstitial Syndrome. (27th October 2022) - Smargiassi, Andrea; Zanforlin, Alessandro; Perrone, Tiziano; Buonsenso, Danilo; Torri, Elena; Limoli, Giuseppe; Mossolani, Elisa E.; Tursi, Francesco; Soldati, Gino; Inchingolo, Riccardo
Abstract : Although during the last few years the lung ultrasound (LUS) technique has progressed substantially, several artifacts, which are currently observed in clinical practice, still need a solid explanation of the physical phenomena involved in their origin. This is particularly true for vertical artifacts, conventionally known as B‐lines, and for their use in clinical practice. A wider consensus and a deeper understanding of the nature of these artifactual phenomena will lead to a better classification and a shared nomenclature, and, ultimately, result in a more objective correlation between anatomo‐pathological data and clinical scenarios. The objective of this review is to collect and document the different signs and artifacts described in the history of chest ultrasound, with a particular focus on vertical artifacts (B‐lines) and sonographic interstitial syndrome (SIS). By reviewing the possible physical and anatomical interpretation of the signs and artifacts proposed in the literature, this work also aims to bring order to the available studies and to present the AdET (Accademia di Ecografia Toracica) viewpoint in terms of nomenclature and clinical approach to the SIS.